Estimating Economic and Environmental Benefits of Urban Trees in Desert Regions - Isaifan, Rima J.; Baldauf, Richard W. (Frontiers in Ecology and Evolution, 2020)
Trees in urban areas have a significant impact on air quality and other environmental issues. Trees can affect the concentration of air pollutants that we breathe in by directly removing pollutants or avoiding emissions and secondary pollutant formation in the atmosphere. In addition, trees have other benefits including increasing property value, intercepting storm water runoff and saving energy needed for cooling of buildings in hot seasons. In this work, we estimate economic and environmental benefits of three tree species typical for desert regions such as Acacia tortilis, Ziziphus spina-christi and Phoenix dactylifera. The benefits varied by species with Acacia tortilis having the highest overall benefits, mostly because of its large leaf surface area and canopy shape. Tree benefits from carbon reduction reached up to US 14 billion annually. Mature trees tended to be more beneficial than smaller trees for improving environmental conditions. The location of trees had minimal impact on the overall economic value. This assessment provides urban planners, foresters, and developers in desert regions with the information needed to make informed decisions on the economic and environmental benefits of urban tree planting.